Improving sarcopenia in older adults: a systematic review and meta-analysis of randomized controlled trials of whey protein supplementation with or without resistance training - Ming-Lin Li; Fei Zhang; Han-Yong Luo; Zi-Wei Quan; Yi-Fei Wang; Le-Tian Huang; Jia-He Wang (Elsevier, 2024)
Objectives: The aim of the study was to comprehensively analyze the effects of whey protein (WP)-enriched supplement intake with or without resistance training (RT) in older patients, either from the community or hospital, who were diagnosed with sarcopenia according to the EWGSOP or AWGS criteria. Methods: This meta-analysis study was registered in PROSPERO (CRD42023407885). We searched the PubMed, Embase, Web of Science, and Cochrane Library databases for RCTs up to June 1, 2023. Standardized mean differences (SMD) with 95% confidence intervals (CI) were used to estimate the pooled results. Results: Ten RCT studies, including 1154 participants, were included and analyzed. The primary outcomes were the changes in muscle mass, strength, and physical performance. In WP group versus (vs.) Isocaloric placebo (PLA)/Routine consultation (RC) group, WP significantly increased the appendicular skeletal muscle mass index (SMD: 0.47, 95%CI: 0.23, 0.71), appendicular skeletal muscle mass (SMD: 0.28, 95%CI: 0.11, 0.45) and gait speed (SMD: 1.13, 95%CI: 0.82, 1.44) in older patients with sarcopenia. In WP with RT group vs. PLA/ RC group, there was significant increase in handgrip strength (SMD: 0.67, 95%CI: 0.29, 1.04). In addition, in the secondary outcomes, WP significantly reduced interleukin-6, significantly increased insulin-like growth factor-1 and albumin, promoted participants' intake of total energy and protein, enhanced activities of daily living scores in patients, and had no significant effect on BMI, weight, or fat mass. Conclusion: This review confirms that WP can improve various aspects of older adult with sarcopenia, thereby enhancing their overall physical condition. More studies should be conducted to validate this result and further explore the effects of WP and RT in patients with sarcopenia.